1.
a^3-(a^3-3a^2 \times 5+3a \times 5^2-5^3)=35 \\
a^3-(a^3-15a^2+3a \times 25-125)-35=0 \\
a^3-(a^3-15a^2+75a-125)-35=0 \\
a^3-a^3+15a^2-75a+125-35=0 \\
15a^2-75a+90=0 \\ 15a^2-5a+6=0 \\ " alt="1. \: a^3-(a-5)^3=35 \\
a^3-(a^3-3a^2 \times 5+3a \times 5^2-5^3)=35 \\
a^3-(a^3-15a^2+3a \times 25-125)-35=0 \\
a^3-(a^3-15a^2+75a-125)-35=0 \\
a^3-a^3+15a^2-75a+125-35=0 \\
15a^2-75a+90=0 \\ 15a^2-5a+6=0 \\ " align="absmiddle" class="latex-formula">
Получаем:
a1+a2=-(5)=5
a1xa2=-(5)=6
a1=3
a2=2
Если: а=3
b=а-5=3-5=-2
Если: а=2
b=а-5=2-5=-3
Тогда:
аb=3*(-2)=-6
аb=2*(-3)=-6
Ответ: аb=-6